2018
DOI: 10.1021/acs.molpharmaceut.8b00132
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Activatable Phthalocyanine–Poly-L-Glutamic Acid Conjugate: Enhanced in Vivo Safety and Antitumor Efficacy toward an Effective Photodynamic Cancer Therapy

Abstract: We previously developed a new zinc(II) phthalocyanine (ZnPc) derivative (Pc 1) conjugated to poly-L-glutamic acid (PGA) (1-PG) to address the limitations of ZnPc as part of an antitumor photodynamic therapy approach, which include hydrophobicity, phototoxicity, and nonselectivity in biodistribution and tumor targeting. During this study, we discovered that 1-PG possessed high near-infrared (NIR) light absorptivity (λ = 675 nm), good singlet oxygen generation efficiency in an aqueous environment, and enhanced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…route, which, barring the case of intraperitoneal chemotherapy, represents a more clinically translatable route to deliver cancer therapies. In the OximUNO system, drug release studies revealed only 15% DOX release, which agrees with our previous studies 48,50 but suggests room for improvement, which may come from using longer polymer-drug linkers such as EMCH (N-ε-maleimidocaproic acid hydrazide) moiety 48,50 or from the use of external triggers [83][84][85] . Unexpectedly, we failed to observe a significant increase in DOX release in the presence of cathepsin B with respect to the hydrolytic conditions; we hypothesise that the nanoconjugate conformation slows down proteolytic degradation, hampering in vitro quantification within the studied timeframe 47 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…route, which, barring the case of intraperitoneal chemotherapy, represents a more clinically translatable route to deliver cancer therapies. In the OximUNO system, drug release studies revealed only 15% DOX release, which agrees with our previous studies 48,50 but suggests room for improvement, which may come from using longer polymer-drug linkers such as EMCH (N-ε-maleimidocaproic acid hydrazide) moiety 48,50 or from the use of external triggers [83][84][85] . Unexpectedly, we failed to observe a significant increase in DOX release in the presence of cathepsin B with respect to the hydrolytic conditions; we hypothesise that the nanoconjugate conformation slows down proteolytic degradation, hampering in vitro quantification within the studied timeframe 47 .…”
Section: Discussionsupporting
confidence: 86%
“…Beyond TAM depletion, we show that St-PGA-mUNO represents an attractive platform to carry additional therapeutic payloads other than DOX, which could include M2M1 polarising agents such as TLR7 agonists 44,91 , beta-emitting radiotherapeutic agents such as dodecanetetraacetic acid-chelated 177 Lu 92 , or photosensitisers used in photodynamic therapy [83][84][85] . We also envisage the combination of TAM-depletion via OximUNO administration together with current chemotherapy regimens to prevent dissemination and relapse, or the use of OximUNO prior to surgery, i.e., as neoadjuvant chemotherapy Taking OximUNO as a proof-of-concept, our data support the peptide-targeted St-PGA design reported here as a new targeted nanosystem that could target other receptors by exchanging the targeting peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a series of NIR-activatable nanocarriers based poly-L-glutamic acid with Pc conjugates in a side chain has been reported for cancer PDT [ 147 , 148 ]. These nanosystems possessed an excellent light-dark toxicity ratio compared to free ZnPc.…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%
“…[32] These structures, alongside their linear analogues, have been broadly investigated for various applications in biomedicine. [33][34][35][36] Nevertheless, the MW of the star-shaped PGAs is still limited in size, in this case by the small number of arms. Recently, bottlebrush-type poly(norbornene)-graft-PGA has been reported.…”
mentioning
confidence: 99%